Cell Cycle Deregulation and TP53 and RAS Mutations Are Major Events in Poorly Differentiated and Undifferentiated Thyroid Carcinomas - Pita, Jaime Miguel (2014)
Background: Anaplastic thyroid carcinomas (ATCs) are among the most lethal malignancies, for which there is no effective treatment. Objective: In the present study, we aimed to elucidate the molecular alterations contributing to ATC development and to identify novel therapeutic targets. Design: We profiled the global gene expression of five ATCs and validated differentially expressed genes by quantitative RT-PCR in an independent set of tumors. In a series of 26 ATCs, we searched for pathogenic alterations in genes involved in the most deregulated cellular processes, including the hot spot regions of RAS, BRAF, TP53, CTNNB1 (beta-catenin), and PIK3CA genes, and, for the first time, a comprehensive analysis of components involved in the cell cycle {[}cyclin-dependent kinase (CDK) inhibitors (CDKI): CDKN1A (p21(CIP1)); CDKN1B (p27(KIP1)); CDKN2A (p14(ARF), p16(INK4A)); CDKN2B (p15(INK4B)); CDKN2C (p18(INK4C))], cell adhesion (AXIN1), and proliferation (PTEN). Mutational analysis was also performed in 22 poorly differentiated thyroid carcinomas (PDTCs). Results: Expression profiling revealed that ATCs were characterized by the underexpression of epithelial components and the up regulation of mesenchymal markers and genes from TGF-beta pathway, as well as, the overexpression of cell cycle-related genes. In accordance, the up regulation of the SNAI2 gene, a TGF-beta-responsive mesenchymal factor, was validated. CDKN3, which prevents the G(1)/S transition, was significantly up regulated in ATCs and PDTCs and aberrantly spliced in ATCs. Mutational analysis showed that most mutations were present in TP53(42% of ATCs; 27% of PDTCs) or RAS (31% of ATCs; 18% of PDTCs). TP53 and RAS alterations showed evidence of mutual exclusivity (P = .0354). PIK3CA, PTEN, and CDKI mutations were present in 14%-20% of PDTCs, and in 10%-14% of ATCs. BRAF, CTNNB1, and AXIN1 mutations were rarely detected. Conclusion: Overall, this study identified crucial roles for TP53, RAS, CDKI, and TGF-beta pathway, which may represent feasible therapeutic targets for ATC and PDTC treatment.}